Standardized in vitro bleeding tests in a non-coated novel hybrid prosthesis for frozen elephant trunk demonstrates minimal oozing during full heparinization, supported by clinical data - Jakob, Heinz; Leins, Timo; Avci-Adali, Meltem; Schlensak, Christian; Wendt, Daniel; Mehta, Yatin; Thielmann, Matthias; Görlinger, Klaus; Song, Suk-Won; Tsagakis, Konstantinos (Frontiers in Cardiovascular Medicine, 2023)
Recent reports questioned blood impermeability of the novel Frozen Elephant Trunk (FET) device, E-vita Open NEO © (EO-NEO). Therefore, standardized in-vitro bleeding tests using porcine heparinized blood were performed, as well as stress testing on blood tightness of the collar sutureline, to investigate this observation.Material and Methods: EO-NEO prostheses were examined in-vitro for blood permeability in 3 test series. Initially, antegrade perfusion with heparinized porcine blood -activated clotting time (ACT) 500s, 60 minutes duration) was performed, followed by ante/retrograde testing via the EO-NEO sideport. Testing of the collar suture line under 10 Newton (N) tension within a suspension device (blood pressure 120mmHg, ACT 560s, 1 minute duration) with the suture material force fiber white (FFWs) yarn using standard fixation (5 stitches/cm), the FFWh yarn in hemostatic fixation (15 stitches/cm) and the flow weave yarn (FWYh).Results: Blood permeability testing of EO-NEO through the prosthetic lumen or via the side port demonstrated minor leakage without statistical difference between standard versus hemostatic suturelines or suture materials used, or positioning on the crimped or tapered portion (p>0.05). The specific collar anastomosis testing demonstrated leakage volumes of 140 mL/min for FFWs versus 16 mL/min for FFWh (p=0.02), versus 9 mL/min with the FWYh (p=0.01).Different blood leakage tests showed minimal oozing and no difference in blood loss through the fabric and different collar suturelines, but unphysiological pressurized retrograde perfusion of the collar region showed significantly less leakage using FWYh and FFWh, prompting production modification of EO-NEO. Clinical results confirmed low blood loss using this novel FET device.